2014
DOI: 10.1007/s00115-014-4115-6
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiologie der Schizophrenie

Abstract: During recent years improved methods in neuroimaging, molecular biology and genetics contributed to new insights into the neurobiology of schizophrenia. This review summarizes and discusses current findings and their impact on the pathophysiology of the disease. New magnetic resonance imaging (MRI) based methods allow investigation of small subregions of the hippocampus and structural and functional connectivity analyses using multimodal imaging approaches. Volume deficits are correlated with MRI spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Oligodendrocytes have glutamatergic n-methyl-D-aspartate (NMDA) receptors, and our group showed that NMDA receptor hypofunction after MK-801 treatment of human cell cultures causes oligodendrocyte dysfunction by inducing deficits in glycolysis [51]. MK-801 is a potent NMDA receptor antagonist, and treatment with this class of antagonists represents the most reliable pharmacological model of the cognitive, positive, and negative symptoms of SZ [52,53]. Therefore, NMDAR antibodies, as part of an inflammatory process, may influence oligodendrocyte pathology.…”
Section: The Intercellular Interactions Of Oligodendrocytes With Micrmentioning
confidence: 99%
“…Oligodendrocytes have glutamatergic n-methyl-D-aspartate (NMDA) receptors, and our group showed that NMDA receptor hypofunction after MK-801 treatment of human cell cultures causes oligodendrocyte dysfunction by inducing deficits in glycolysis [51]. MK-801 is a potent NMDA receptor antagonist, and treatment with this class of antagonists represents the most reliable pharmacological model of the cognitive, positive, and negative symptoms of SZ [52,53]. Therefore, NMDAR antibodies, as part of an inflammatory process, may influence oligodendrocyte pathology.…”
Section: The Intercellular Interactions Of Oligodendrocytes With Micrmentioning
confidence: 99%
“…In a survey using the standard Spider Phobia Questionnaire (SPQ), 10.3% out of 3 863 Czech respondents reported very high fear of spiders (scoring 22 or higher on 31-point scale; [ 13 , 14 ]). Arachnophobia, an irrational, uncontrollable fear of spiders, is one of the most common specific animal phobias affecting 2.7–6.1% of general population, women significantly more often than men [ 15 , 16 ]. These negative emotions associated with spiders are even more intriguing since only 0.5% of all spider species represent a real potential threat to humans [ 17 ].…”
Section: Introductionmentioning
confidence: 99%